Advantages of water droplet machining over abrasive waterjet cutting of carbon fiber reinforced polymer. (September 2022) - Mitchell, Benjamin; Sadek, Ahmad; Kinsey, Brad
Abstract: The cutting of carbon fiber reinforced polymer (CFRP) sheets with conventional tooling, such as an end-mill, results in excessive tool-wear, high-heat generation, and dust emission. Abrasive waterjet (AWJ) cutting has been used as an alternative method; however, this technique often leads to delamination of the composite material, especially around the pierce locations. Moreover, AWJ requires considerable post processing of the machined part to remove residual abrasive particles in addition to the high nozzle and conduit wear rates. A new advancement in pure waterjet cutting, Water Droplet Machining (WDM), has shown success in cutting CFRP sheets without the detrimental effects of delamination. In this paper, the results of cutting 5.5mm-thick CFRP sheet are presented using an AWJ and the WDM process. The cutting performance of the two methods is assessed based on the surface roughness of the cut edge, the presence of delamination, and the geometric accuracy of a variety of basic shapes cut from the sheet.